The Impact of Biochar and FeCl3 Administration on Fe Toxicity Symptoms and Productivity of Bok Choy Mustard Plants (Brassica rapa L.) Nauli Variety - Ratna Apriliani Prameswari; Yulita Nurchayati; Nintya Setiari (Jurnal Ilmu Pertanian Indonesia, 2025)
Fe³⁺ pollution is a factor that reduces bok choy production. Its productivity can be increased by adding biochar, which can adsorb inorganic ions, including iron. This study examines the impact of rice husk biochar and FeCl₃ on bok choy productivity, using a completely randomized design with a 3´3 factorial pattern. The first factor was the concentration of rice husk biochar (0, 2.5, and 7.5 g/kg), and the second was the concentration of FeCl₃ (0, 25, and 50 mg/L). The criteria measured were the number of leaves, leaf area, chlorophyll content, and vitamin C levels. The combination of 0 g/kg biochar and 0 mg/L FeCl₃ proved to be the most effective treatment for boosting bok choy growth. The treatment yielded 12.6 leaf count, 73.3 cm² leaf area, 2.0 mg/g chlorophyll, and 30.8 ppm vitamin C. Fe³⁺ treatments at 25–50 mg/L drastically lowered all growth metrics. The applied biochar doses were insufficient to efficiently absorb Fe³⁺ and boost the yield of bok choy. Keywords: biochar, bok choy, chinese mustard, FeCl3, toxicity